A Study on the Mechanical Properties and Bursting Liability of Coal-Rock Composites with Seam Partings - Dong Xu; Mingshi Gao; Yongliang He; Xin Yu (Advances in Civil Engineering)
Geological tectonic movements, as well as complex and varying coal-forming conditions, have led to the formation of rock partings in most coal seams. Consequently, the coal in coal-rock composites is characterised by different mechanical properties than those of pure coal. Uniaxial compression tests were performed in this study to determine the mechanical properties and bursting liability of specimens of coal-rock composites (hereinafter referred to as “composites”) with rock partings with different dip angles θ and thicknesses D. The results showed that as θ increased, the failure mode of the composite changed from tensile and splitting failure to slip and shear failure, which was accompanied by a decrease in the brittleness of the composite and an increase in its ductility as well as a decrease in the extent of fragmentation of the coal in the composite. Additionally, as θ increased, the uniaxial compressive strength σu, elastic modulus E, and bursting energy index Ke of the composite decreased. The rock parting in the composite was the key area in which elastic energy accumulated. As D increased, σu, E, and Ke of the composite increased. In addition, as D increased, the ductility of the composite decreased, and the brittleness and extent of coal fragmentation in the composite increased. Notably, the curve for the cumulative acoustic emission (AE) counts of the composite corresponding to the stress-strain curve could be divided into four regimes: pore compaction and closure, a slowly ascending linear elastic section, prepeak steady crack propagation, and peak unsteady crack propagation. The experimental results were used to propose two technologies for controlling the stability of coal-rock composites to effectively ensure safe and efficient production at working faces.